Developmental Biology of Forensically Important Beetle, Necrophila (Calosilpha) brunnicollis (Coleoptera: Silphidae) - Jakubec, Pavel; Qubaiová, Jarin; Novák, Martin; Růžička, Jan (Journal of medical entomology, 2021)
The postmortem interval (PMI) estimation, in cases where the body was discovered in an advanced stage of decomposition, is predominantly based on entomological evidence. However, very few forensically important species are sufficiently known in detail to allow a practical application. One of them is the carrion beetle, Necrophila (Calosilpha) brunnicollis (Kraatz, 1877). Its development from egg to adulthood was studied under a range of ecologically relevant constant temperatures to find parameters of thermal summation models. Developmental sexual dimorphism and the presence of developmental rate isomorphy were investigated. Herein we present the lower developmental thresholds and sum of effective temperatures for all developmental stages of N. brunnicollis (egg, first-third larval instar, postfeeding stage, and pupae). We did not find any evidence of developmental sexual dimorphism nor was the presence of developmental rate isomorphy confirmed. Our results present the first thermal summation model of the East Asian carrion beetle that can be used for the PMI estimation.
Keywords: brouci; mrtvola; Cadaver; zvláštnosti životní historie; sexual dimorphism; sexuální faktory; developmental rate; Silphinae; kukla; forenzní entomologie; teoretické modely; Postmortem Changes; Pupa; Models, Theoretical; thermal summation model; zvířata; Temperature; Coleoptera; Sex Factors; Life History Traits; posmrtné změny; larva; Larva; Forensic Entomology; teplota; forensic entomology; Animals